Medicinal plants of the local communities around Gunung Jagoi in Bau district - Julan, Baling (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study was carried out around Mount Jagoi in Bau District involving two villages to document the various kinds of medicinal plants used by the local communities. The uses and the methods of preparation of the medicinal plants also recorded. It was carried out through interview with the respondents and collection and identification of medicinal plants in the study area. A total of 58 species of medicinal plants belonging to 38 families were identified and documented with the help of local informers as well as women in the villages. 46 species (79%) were wild plants while 12 species (21%) were cultivated plants. A majority of species are herbaceous angiosperms followed by shrubs and trees. The most common part of plant used in preparing herbal medicine is the leaves. More plants are used for general health to treat hypertension, flatulence, skin diseases and injuries, stomachache and headache. The most common method of preparation is decoction, followed by infusion and poultice. Among the species studied, the most frequent used as a medicine come from family of Zingiberaceae, Fabaceae and Piperaceae.